Legal Responsibility of Land Deed Officials in Overcoming Abuse of Land Sale and Purchase Deeds - Noor, Aslan; Nurfaridah; Purnama, Selly; Meliani, Indri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The Deed of Sale and Purchase (AJB) is a critical element in land transactions in Indonesia, requiring legal validity to ensure the certainty of land ownership status. However, the misuse of AJB, including document forgery by the Land Deed Official, has led to legal disputes that harm various parties and undermine public trust in the land law system. This study aims to analyze the legal responsibility of The Land Deed Official in addressing the misuse of AJB by identifying obstacles in task execution and potential violations. The research method used is a qualitative approach with case studies of land disputes involving The Land Deed Official, as well as an analysis of relevant regulations related to the duties and supervision of The Land Deed Official. The study also aims to provide policy recommendations to enhance The Land Deed Official accountability and strengthen a more transparent and accountable land system. The Land Deed Official plays an essential role in ensuring the legality of land sale transactions in Indonesia by verifying related documents, such as land certificates and tax payment evidence, in accordance with applicable regulations. Misuse of the AJB by The Land Deed Official can undermine legal certainty, trigger land disputes, and hinder economic growth. To prevent this, stricter supervision, the application of technology for transparency, and strict enforcement of sanctions in the land system are required.